2019
DOI: 10.1155/2019/2893043
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Recurrence from Radiation Necrosis in Gliomas Based on the Radiomics of Combinational Features and Multimodality MRI Images

Abstract: Purpose To classify radiation necrosis versus recurrence in glioma patients using a radiomics model based on combinational features and multimodality MRI images. Methods Fifty-one glioma patients who underwent radiation treatments after surgery were enrolled in this study. Sixteen patients revealed radiation necrosis while 35 patients showed tumor recurrence during the follow-up period. After treatment, all patients underwent T1-weighted, T1-weighted postcontrast, T2-weighted, and fluid-attenuated inversion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…The model performed well in both training and validation datasets with an AUC of 0.988 and 0.914, respectively. A similar model based on 51 glioma patients developed by Quan Zhang et al ( 19 ) achieved outstanding performance with an AUC of 0.962 following validation. However, to the best of our knowledge, this is the first multiparametric model developed to predict recurrence in LGG before surgery.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The model performed well in both training and validation datasets with an AUC of 0.988 and 0.914, respectively. A similar model based on 51 glioma patients developed by Quan Zhang et al ( 19 ) achieved outstanding performance with an AUC of 0.962 following validation. However, to the best of our knowledge, this is the first multiparametric model developed to predict recurrence in LGG before surgery.…”
Section: Discussionmentioning
confidence: 92%
“…Mutations of the isocitrate dehydrogenase (IDH)1/2 genes are common events in gliomas ( 27 ), especially among grade II gliomas, where IDH1 mutations are observed in about 70% to 80% of cases ( 27 , 28 ). Some studies indicated that IDH1 mutation status could improve OS and PFS in grade II and III glioma ( 19 , 29 ). Although the IDH1 mutation has been identified as an independent positive prognostic biomarker for survival in patients with glioma ( 26 , 30 ), the association between the IDH mutant status and the risk of developing recurrence is still not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although histological analysis is the gold criteria for glioma grading, there is a main reason to illustrate that is not absolutely reliable: the tumor may contain high-grade lesions, pathological specimens resected during primary surgery could not completely re ect the nature of the whole tumor.Hence,relied on radiomics technology,we could extract numerous image parameters from the whole tumor region and quantitatively analyse the tumor properties.many previous studies have demonstrated that the application of radiomics technology can effectively differentiate high and low grade gliomas [17][18];Quan,Z et al [19]used 51 LGG patients and developed the radiomics model to differentiate recurrence from radiation necrosis in gliomas,these previous studies could provide reference for strategy determine.In our study,64 LGG cases were used to establish radiomics models and also yield an optimal performance.It is conducive to clinician to develop more accurate treatment plans and prognosis evaluation for patients with high risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proven that some molecular alterations show great predictive and prognostic value in gliomas recurrence,numerous studies have shown that in grade II ~ III gliomas ,1p/19q chromosomal codeletion is associated with improved PFS and OS.Similarly, IDH mutations are a good prognostic marker for OS improvement in grade II ~ III glioma [19,24].However, it's not satisfying to predict the recurrence of LGG only based on genotype alone [15].More accurate predictions require us to develop.Therefore,base on the MRI technology and numerous image features,we developed a radiomics methods to discriminate the recurrence LGG and non-recurrence LGG.According to our study the combination model of multi-parametric MRI features yield a AUC of 0.966 in testing set and 0.93 in validation set,these results were obviously better than the individual MRI sequence model;in addition, the DCA showed that the net bene t of using a radiomics nomogram constructed on the basis of all three sequences was higher than any single sequence,it demonstrated that the nomogram we constructed is worthy of clinical use.…”
Section: Discussionmentioning
confidence: 99%